Linear psoriasis-a rare presentation - Rahaman, Md Mahabubur; Islam, Md Aminul; Ullah, Md Rahmat; Barbhuiyan, Md Zahed Parvez (Northern International Medical College Journal, 2015)
Abstract not available Northern International Medical College Journal Vol.6(1) 2014: 36-37